Restoration of ecosystem services through afforestation on degraded sodic lands in Indo-Gangetic plains - Singh, YASH PAL; Singh, GUrbachan; Mishra, Vinay K; Arora, Sanjay; Singh, Bajrang; Gupta, Ravindra K (The Indian Journal of Agricultural Sciences, 2019)
Afforestation with tree species on a highly degraded sodic lands in Lucknow (26° 47’ N; 80°46’ E), Uttar Pradesh, India has improved the provisional biomass production and supportive (nutrient dynamics and soil ameliorative) services during ten years. Of the ten species studied, Prosopis juliflora produced highest (56.5 t/ha) above ground biomass at ten years age. P. juliflora had highest total N P K accumulation followed by Acacia nilotica, Casuarina equisetifolia, Terminalia arjuna, Pithecellobium dulce and Pongamia pinnata whereas, total Ca and Mg contents were relatively high in T. arjuna followed by P. juliflora, A. nilotica and C. equisetifolia. Tree leaves reported the highest nutrient concentration followed by branches and stem. P. juliflora, A. nilotica and P. pinnata were found more efficient in nitrogen recycling compared to other species. Corresponding to biomass production, P. juliflora also dominated in nitrogen uptake. However, nitrogen retranslocation was highest in C. equisetifolia. P. juliflora, although produced maximum areal biomass, was not as good in nitrogen use efficiency (NUE), indicating that it produced relatively less biomass per unit of N uptake. T. arjuna had the greatest phosphorus use efficiency (PUE) and the lowest infiltration rate and chemical indicators (pH, ESP) of sodic soils after ten years of planting was recorded with P. juliflora which was 20.12%, 557.50% and 9.23%, 48% higher over the initial and 9.02%, 122% and 7.29% , 43.2% higher over natural fallow respectively. Microbial biomass was relatively higher under C. equisetifolia and P. juliflora than rest of the tree species.